Diversity changes of microbial communities into hospital surface environments. Issue 7 (July 2017) - Yano, Rika; Shimoda, Tomoko; Watanabe, Reina; Kuroki, Yasutoshi; Okubo, Torahiko; Nakamura, Shinji; Matsuo, Junji; Yoshimura, Sadako; Yamaguchi, Hiroyuki
Abstract: Previous works have demonstrated considerable variability in hospital cleanliness in Japan, suggesting that contamination is driven by factors that are currently poorly controlled. We undertook 16S rRNA sequence analysis to study population structures of hospital environmental microbiomes to see which factor(s) impacted contamination. One hundred forty-four samples were collected from surfaces of three hospitals with distinct sizes ("A": >500 beds, "B": 100–500 beds, "C": <100 beds). Sample locations of two ward types (Surgical and Internal) included patient room bed table (multiple) (4BT), patient overbed table (multiple) (4OT), patient room sink (multiple) (4S), patient room bed table (single) (SBT), patient overbed table (single) (SOT), patient room sink (single) (SS), nurse desk (ND), and nurse wagon (NW). Total DNA was extracted from each sample, and the 50 samples that yielded sufficient DNA were used for further 16S rRNA sequencing of hospital microbiome populations with cluster analysis. The number of assigned bacterial OTU populations was significantly decreased in hospital "C" compared to the other hospitals. Cluster analysis of sampling locations revealed that the population structure in almost all locations of hospital "C" and some locations in the other hospitals was very similar and unusually skewed with a family, Enterobacteriaceae . Interestingly, locations included patient area (4OT, 4BT, SBT) and nurse area (ND), with a device (NW) bridging the two and a place (4S and SS) shared between patients or visitors. We demonstrated diversity changes of hospital environmental microbiomes with a skewed population, presumably by medical staff pushing NWs or sinks shared by patients or visitors.